Proxemics mobile collocated interactions - Porcheron, Martin; Lucero, Andrés; Quigley, Aaron; Marquardt, Nicolai; Clawson, James; O'Hara, Kenton (2016)
Recent research on mobile collocated interactions has been looking at situations in which collocated users engage in collaborative activities using their mobile devices. However, existing practices fail to fully account for the culturally-dependent spatial relationships between people and their digital devices (i.e. the proxemic relationships). Building on the ideas of proxemic interactions, this workshop is motivated by the concept of 'proxemic mobile collocated interactions', to harness new or existing technologies to create engaging and interactionally relevant experiences. Such approaches would allow devices to not only react to presence and interaction, but also other indicators, such as the interpersonal distance people naturally use in everyday life. The aim of this one-day workshop is to bring together a community of researchers, designers and practitioners who are interested in exploring proxemics and mobile collocated interactions.